(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2023)
The aim of the research was to identify the level of social stigma and depression among patients with the Corona pandemic (Covid-19). And study the correlation between social stigma and depression. And the detection of differences according to the two variables of the research: (gender, economic level of the family). It adopted the descriptive analytical approach, used a measure of social stigma (MICHAEL, KING, et al, 2007), and a scale of depression (Birleson Scale-Questionnaire), and the research sample included (112) male and female patients from the Corona pandemic (Covid-19) who ranged in age from Between (21-40) years old. Among the most important results of the research: the presence of a high level of social stigma according to the estimation of the members of the research sample of patients with the Corona pandemic (Covid-19). And the presence of a high level of depression for them, and a positive and statistically significant correlation between the answers of the research sample members in the social stigma scale and their scores on the depression scale. And there were no differences on the social stigma scale and the depression scale according to the gender variable.